ARBITRARY DURATION PULSE SHAPER - OSOLINSKY, Oleksandr; KOCHAN, Volodymyr; SACHENKO, Anatoliy; KOCHAN, Orest; KOCHAN, Roman (Herald of Khmelnytskyi National University. Technical sciences, 2022)
This paper considers the possibility of constructing a universal pulse generator based on TTL (transistor-transistor logic) elements, which provides pulses of a given duration at the time of entry to the input of the negative edge of the input start pulse (difference from logical unit to logical zero). The duration of the generated output pulse can be set by the capacitance of one capacitor and does not depend on the duration of the input pulse. A significant advantage of the proposed pulse shaper is the high steepness of both the positive front (difference from logical zero to logical unit) and the negative edge of the generated output pulse (difference from logical unit to logical zero), which depends only on the operation time of logical elements and not depends on the duration of both input (start) and output pulses. This advantage is based on the action of positive feedback at the time of formation of both positive and negative fronts of the output pulse. In this case, the feedback circuits in the formation of positive and negative fronts of the output pulse are different, which does not allow the circuit to switch to self-excitation mode (autogeneration). The advantages of the proposed pulse shaper (high steepness of the fronts with little complication of the circuit compared to the known capacitor pulse shapers) are determined by using the internal structure of the logic elements of the TTL series. This paper also considers the possibility of reducing the capacitance of the capacitor by several tens of times, which determines the duration of long output pulses, due to the introduction of an emitter repeater. The main disadvantage of the proposed pulse shaper is the low temperature and time stability of the duration of the formed output pulse, which is characteristic of all capacitor pulse shapers.
Keywords: pulse shaper; pulses of a given duration; pulse duration; TTL